A forty year journey: The generation and roles of NO in plants - Kolbert, Zs; Barroso, J B; Brouquisse, R; Corpas, F J; Gupta, K J; Lindermayr, C; Loake, G J; Palma, J M; Petřivalský, M; Wendehenne, D; Hancock, J T (Nitric oxide, 2019)
In this year there is the 40th anniversary of the first publication of plant nitric oxide (NO) emission by Lowell Klepper. In the decades since then numerous milestone discoveries have revealed that NO is a multifunctional molecule in plant cells regulating both plant development and stress responses. Apropos of the anniversary, these authors aim to review and discuss the developments of past concepts in plant NO research related to NO metabolism, NO signaling, NO's action in plant growth and in stress responses and NO's interactions with other reactive compounds. Despite the long-lasting research efforts and the accumulating experimental evidences numerous questions are still needed to be answered, thus future challenges and research directions have also been drawn up.
Keywords: Symbiosis; rostliny; Nitric Oxide Synthase; signální transdukce; Reproduction; Plant Development; Plant Physiological Phenomena; nitrátreduktasa; Signal Transduction; vývoj rostlin; Plants; synthasa oxidu dusnatého; oxid dusnatý; symbióza; Nitric Oxide; fyziologie rostlin; rozmnožování; Nitrosative Stress; Nitrate Reductase; nitrosativní stres